Analisis Asuhan Keperawatan Pada Lansia dengan Gastritis di Panti Griya Lansia Jannati - Ferawati Gintulangi; Rosmin Ilham; Hamna Vonny Lasanuddin; Marlina Malik (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
In the body is needed a balanced amount of stomach acid, excessive stomach acid causes erosion of the gastric mucosa causing pain in the epigastric area and causing gastritis. The elderly with gastritis are a vulnerable population and changes in the lifestyle of the elderly discomfort due to gastritis which often recurs due to peptic ulcers. The purpose of this study was to be able to provide and apply nursing care in the elderly with gastritis. Descriptive quantitative research method, a sample of 3 people who met the sample criteria, the instrument used is a nursing care sheet, the data analysis technique used was descriptive statistical analysis. The findings of the study were obtained from the assessment of complaints felt between client 1, client 2 and client 3 at the time of the assessment had similarities where there were complaints of pain in the heartburn, pain felt like being stabbed, pain was lost, pain caused by poor diet. Nursing diagnoses include acute pain, knowledge deficit, nausea and anxiety. Nursing action planning and nursing implementation are carried out based on observation, therapeutic, education and co-widening. Nursing evaluation found that the nursing problems experienced by 12 patients were resolved.